Frailty in Patients With Lung Cancer: A Systematic Review and Meta-Analysis - Komici, Klara; Bencivenga, Leonardo; Navani, Neal; D'Agnano, Vito; Guerra, Germano; Bianco, Andrea; Rengo, Giuseppe; Perrotta, Fabio (Chest, 2022)
Previous studies regarding the prevalence of frailty in patients with lung cancer and mortality in frail patients with lung cancer are inconsistent and require clarification. What is the prevalence and impact of frailty in patients with lung cancer? This systematic review and meta-analysis used a combination of free-text terms and medical subject headings terms, according to the database requirements in MEDLINE/PubMed, Scopus, and Cochrane Library from inception until November 15, 2020. A total of 2,571 articles were identified, and 16 articles involving 4,183 patients were included for study. The prevalence of frailty in lung cancer was 45% (95% CI, 28-61; I = 99.5%; P < .0001). In patients with lung cancer, frailty was associated with an increased hazard ratio for mortality (hazard ratio, 3.01; 95% CI, 1.77-5.10; P < .001). The prevalence of frailty in lung cancer is 45%, which has a significant negative impact on survival of patients with lung cancer. These results highlight the importance of measuring frailty, which provides important prognostic information, and may provide opportunities for interventions to improve outcomes in patients with lung cancer.